Extended hierarchy-of-effect model and its application on Islamic reality shows towards Malay community in Malaysia - Wok, Saodah; Ismail, Rizalawati; Azman, Zakirah; Latif, Siti Sakinah (2012)

(untitled)
This paper tries to explore the possibility of applying the Hierarchy-of-Effect-Model (Zajonc, 1980) on Islamic reality shows towards Malay community in Malaysia, which is a new phenomenon, compared to the other existing reality shows that are mushrooming. The objectives of the study are (1) To find out the level of attention given to, perception of, attitude towards, involvement in, satisfaction obtained, and impact change from watching Islamic reality shows; (2) To compare the level of effects on different types of viewers (gender and age-group); and (3) To analyze the relationships between all the effect-related variables for the Islamic reality shows towards the Malay community in Malaysia. This study employs a quantitative research design, using survey method, with questionnaire as the research instrument used for data collection. Pilot study has been conducted to pre-test the research instrument. The study is using cluster and stratified random sample, in which the stratified groups are based on state, gender, and age. The data were collected in March 2012. The study found that the two most popular Islamic reality shows are Imam Muda and Akademi Al-Quran. The Malay community has positive perception and attitude towards the Islamic reality shows. They are also satisfied with the programs and above all the programs have positive impact on them. Therefore, the hierarchy of effects model could be applied to the Islamic reality shows for the Malay community in Malaysia; thus, implying that the learning theory is supported, but with a cyclical open system in nature.